Precision Agriculture System with IoT: An Approach to Increase Production and Efficiency - Rif’an, Mochammad; Irianto, Kurniawan Dwi (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The application of IoT technology in the agricultural industry has significantly increased efficiency and productivity. In this study, a smart irrigation system that utilizes soil temperature and humidity sensors and NodeMCU ESP8266 and ESP32 units will be explained for its implementation. The NRF24L01 module is a wireless sensor module used to transmit data wirelessly and allows it to cover a wide range. Now, farmers can monitor and control the irrigation system remotely through the Blynk application. Tests show that crops managed through the IoT system have more consistent soil and air conditions and more efficient temperature and humidity control. Therefore, this precision agriculture system utilizes IoT and NRF24L01 to improve water and energy efficiency and encourage sustainability efforts in addressing climate change and increasing global food demand